Relationship of Gadget Use With Sleep Quality in Pandemy Covid-19 In School Age Children in State Elementary School Goa Jereweh District West Sumbawa - Eka Adithia Pratiwi; Lestari Ananda; Baik Heni Rispawati; Rias Pratiwi Safitri (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Around 1.5 billion children have been dismissed from school due to the outbreak of Covid-19,as a result of which many of them are spending more time using electronic devices during the lockdown.According to data from the American Children's Academy, 75% of 9-10 year olds experience sleep deprivation due to unsupervised use of technology.The purpose of this study was to determine the relationship between gadget use and sleep quality in school age children.This study used a correlation design with a cross sectional approach.The data collection tool used a questionnaire. Data analysis used the Spearman-rho test.The results of this study found that there was no relationship between the use of gadgets and the quality of sleep during the Covid-19 pandemic with a P-Value of 0.653> 0.05 (insignificant). Recommend that parents can increase their activities and activities with children,such as involving children in home activities and exercising together to distract children from gadgets.